HADIST TENTANG IBADAH UMUM DALAM BENTUK LUKISAN KALIGRAFI ARAB - HARI MUKHLAS, Drs, Syafei, M.Ag., Drs. Wisdiarman, M.Pd. (Serupa The Journal of Art Education, 2016)
The high level of criminality and declining moral values at nowadays indicates that the human was oblivious of the aim in life is to seize the afterlife in worship to Allah SWT.Therefore, the author intends to designate the theme of the final work of painting calligraphy relating to the hadith of general worship. The election of general worship as the theme of the final work because of the general worship directly related to human life, with fellow humans and Allah SWT.At the end of work of this hadith about general worship which will be explained in the form of painting art of Arabic calligraphy. The reasons of selecting calligraphy because the author‟s love of calligraphy. Furthermore, this thesis made with the goal of creating a painting calligraphy related to general worship,Based on issues and objectives above, the results obtained in the form of ten calligraphy paintings as a form of final work project related to general worship.Keyword : Hadith of General Worship.